Radiative cooling of hot Cn− and CnH− molecules. (August 2015) - Kaminska, M; Nascimento, R F; Stockett, M H; Anderson, E K; Delaunay, R; Vizcaino, V; Rousseau, P; Adoui, L; Huber, B A; Thomas, R D; Gatchell, M; Hansen, K; et al.
Synopsis: We have measured the rates of neutrals produced from 10 keV C n − or C n H − ( n =2, 4, 6, 8, and 10) ion beams stored in one of DESIREE's 14 K storage rings. For n =4, 6, and 8 we observe marked differences between C n − and C n H − cooling rates as inverse internal conversion [cf. S. Martin et al (2013) Phys. Rev. Lett. 110, 063003] processes are effective for the C n − ions only. Knowledge of the cooling rates of these ions are important for estimates of their formation and destruction rates in cold interstellar environments.